The Causes of not Reporting Medication Errors from the Viewpoints of Nursing in Baharlo Hospital in 2010 - Azar Tol; Abolghasem pourreza; Golamreza sharifirad; Bahram Mohebbi; Zahra Gazi (Tehran University of Medical Sciences, 2010)
Background: Reporting of  medication errors  leads to saving Patients ;apossafety and also is counted as a valuable information source for further prevention of mistake in future.  The aim of this study was to determine the reasons for refusing to report medication errors from the viewpoints of nurses.Material and Methods:In this descriptive study, 140 of 200 nurses who were employees of Baharlo hospital of Tehran participated in the study (response rate = 70%). Data were collected through a questionnaire. Test- retest analysis conducted for measuring reliability of the questionnaire and content and face validity of the instrument confirmed by key statisticians and methodologists. . SPSS software and descriptive statistics were used for analyzing the collected data. Results:Our findings indicate that the reasons of not reporting medication errors were Management factors (3.68 ± 1.12), Fear of reporting outcomes (3.09 ± 1.68) and Process related to reporting (2.73± 1.26). Management factors domain was the major cause of refuse of reporting medication errors. Conclusion:Since medication errors seem to be unavoidable, suppression, decreasing medication error depends on using a systematic approach with emphasis on management and nursing care.